Marketable Branding in Surabaya Mayor Election 2015-2019 - Wahyuni Choiriyati; Ade Tuti Turistiati; Dinda Rakhma Fitriani (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
This article provide a study of theories and concepts regarding the election of Surabaya mayor 2015-2019. The approach used is a comprehensive study of political marketing by Lee Marshment in 2001. Surabaya became the object of the review in this article with various uniqueness of the socialization process of Mayor Election or Pilwali by installing countdown timers and various lanterns in the 2015 Pilwali Surabaya mascot to target beginner voters in Surabaya. Marketable Branding topics are a strategic issue because they involve the way a political institution in formulating a political product, arranging a campaign publication program and political communication, and a segmentation strategy to meet the needs of the society to the price calculation of a political product. The sociocultural conditions of a geographical and demographic area must also be taken into account in the segmentation and formulation of political issues. Surabaya was able to become a kind of role modeling in the preparation of SWOT branding politicians for other regions in Indonesia.